Fisheries co-management: an institutional innovation towards sustainable fisheries industry - Raja Abdullah, Nik Mustapha (2002)
The changes that have occurred in the fishery sector during the past two decades call for a reappraisal of the relevance of conventional fishery development and management strategies. Principal debates on fishery management policies arise from the natural tension between three differing fishery worldviews or paradigms, namely the conservation, rationalization and social/ community paradigms. Several strategies have been adopted worldwide to address the problems of fisheries resource use conflicts and over exploitations, but the outcomes were mixed. Many studies have pointed out that lack of participation of stakeholders/resource users in planning and decision making as the major factor. The fishery co-management as an alternative to centralized command and control fisheries management is often suggested as a solution to the problem. This paper proposes the concept and structure of a fisheries co-management arrangement, and identifies factors affecting the selection of this alternative management institution. Fisheries co-management starts with the premise that stakeholder involvement in the planning and management of natural resources will improve resource conditions and welfare of the society. From the policy perspective, there is a need to empirically evaluate the efficiency and net benefits of co-management institutions against those fisheries that are centrally managed.